Comparison of the Effectiveness of Imago Therapy for Emotional Breakup with Cognitive-Behavioral Therapy Focused on Trauma on Affective Capital and Depression in Adolescent Girls - Fatehi, Mehri; Golparvar, Mohsen; Mahdad, Ali (Journal of Assessment and Research in Applied Counseling (JARAC), 2024)
Objective: Adolescent girls who experience emotional breakups have a pressing need to overcome their difficulties. Accordingly, this study aimed to compare the effectiveness of Imago therapy for emotional breakup with cognitive-behavioral therapy on Affective Capital and depression in adolescent girls. Materials and Methods: This quasi-experimental study was conducted in three phases: pre-test, post-test, and follow-up, with a control group. The statistical population consisted of adolescent girls who experienced emotional breakups in Isfahan in the winter of 2022, from which 48 girls were purposefully selected and assigned to three groups (each group with 16 participants). Golparvar’s Affective Capital Scale (2016) and Beck’s Depression Inventory (1996) were used to measure the dependent variable in three stages. The two therapy groups each underwent ten 90-minute sessions, while the control group received no treatment. Data were analyzed using covariance analysis and Bonferroni post-hoc test through SPSS version 26. Findings: The results showed a significant difference in Affective Capital and depression between the Imago therapy for emotional breakup and cognitive-behavioral therapy groups compared to the control group (p < .01). There was no significant difference between the two therapies in Affective Capital. However, in the follow-up stage, cognitive-behavioral therapy was more effective than Imago therapy for emotional breakup in reducing depression (p < .01). Conclusion: Considering the effectiveness of Imago therapy for emotional breakup and cognitive-behavioral therapy in enhancing Affective Capital and reducing depression, it is recommended that these two therapies be used in psychological treatment centers for adolescent girls who have experienced emotional breakups.